ANALISIS PENGARUH KEEFEKTIFAN KOMUNIKASI, KUALITAS LAYANAN, DAN KEPERCAYAAN - Mulyo Budi Setiawan; Bambang Sudarsono (Jurnal Bisnis dan Ekonomi, 2007)
The development of Indonesian economy has caused the increase of competition for a high educational service industry, especially for private college. Each of it offer some competiting price, exciting service, good quality of services and an interesting physic of the college building. This research is to analize the problems. How is influence of communication effectiveness, service quality, trust to relationship commitment. The population in this research is all the student of STIE STIKUBANK Semarang, which stratified to diploma program (D3), strata one (graduated program or S1) and post graduate program Magistry of Management (S2). The technique which used is Propotional Stratified Sampling Technique to know how the influence of effectiveness communication, service quality, trust to relationship commitment, the writer uses an analizes instrument Structural Equation Model (SEM) which is helped by AMOS version 5.0. The result of this research shows that two hypothesis were not significantly, which effectiveness communication to trust and service quality to relationship commitment. Based on this research the influence of variables as matter of regardinent to promote and offens the relationship commitment. Keywords: Effectiveness Communication, Service Quality, Trust and Relationship Commitment.